Teaching the brain to read [ strategies for improving fluency, vocabulary, and comprehension - Willis, Judy (Gale virtual reference library, 2008)
Get to the heart of teaching your students the reading process with this guide to what happens in the human brain when students learn how to read. Neurologist and middle school teacher Judy Willis connects classroom practice to the neurology of reading and provides whole-class and individualized activities, lessons, and units that you can use in every grade and subject to help all students become better readers